Studies on the Contact System of Coagulation during Therapy with High Doses of Recombinant IL-2: Implications for Septic Shock - Hack, C Erik; Wagstaff, John; Strack Van Schijndel, Robert J M; Eerenberg, Anke J M; Pinedo, Herbert M; Thijs, Lambertus G; Nuijens, Jan H (Thrombosis and Haemostasis, 1991)
Patients treated with high doses of interleukin-2 (IL-2) because of cancer, develop hemodynamic and vasopermeability changes, that resemble those observed in sepsis. These patients thus provide a unique opportunity to study the early events in the development of septic shock. We analysed the changes that occurred in the contact system of coagulation in plasma from 4 patients, who together received seven 12-day cycles of high doses of IL-2. Levels of factor XII and prekallikrein during the cycles progressively fell to 50 and 30% of their initial levels, respectively, whereas significant increases in plasma factor XIIa-and kallikrein-C1-inhibitor complexes were not observed (in 3 out of 211 samples slightly increased levels of both complexes were found). The reductions in factor XII and prekallikrein were only in part due to protein leakage, since levels were still significantly lower, i. e., 80 and 50%, respectively, when corrected for albumin decreases. Levels of high molecular weight kininogen (HMWK) also decreased during IL-2 therapy, however, this decrease paralleled that of albumin. SDS-PAGE analysis of plasma HMWK did not reveal increased cleavage of this protein. The reduction of factor XII and prekallikrein, corrected for protein leakage, significantly correlated with albumin levels and inversely with daily cumulative weight gain in the patients.Thus, we demonstrate that factor XII and prekallikrein decrease during IL-2 therapy. As these decreases, already observed after 1 day treatment, were disproportional to that of albumin, a negative acute phase reactant, and correlated with signs of the vascular leak syndrome, we favor the explanation that they reflected activation rather than a decreased synthesis of the contact system proteins. Further studies are needed to substantiate this hypothesis.